PHILOSOPHICAL-METHODOLOGICAL ASPECTS OF THE PROCESSES OF INFORMATIZATION AND KOMPUTERIZATION OF EDUCATION (Journal of Information Technologies in Education (ITE), 2010)
In the article is considered the maintenance of the processes of informatization and computerization of education, advantages and lacks of certain processes are described, the optimum ways of their realization are pointed out.
Keywords: computer design; computerization of education; informatization